PERKEMBANGAN TEORI DAN PRAKTIK MENGENAI PARLEMEN DI INDONESIA - Andy Omara; Joko Setiono; Muhammad Ibrahim; Faiz Rahman (Faculty of Law, Universitas Gadjah Mada, 2021)
Abstract The idea of a parliament system continues to develop from time to time. There are many thoughts of constitutional law experts which later became the theoretical basis for the implementation of the parliament system in a country, including in Indonesia. Furthermore, the existence of representative institutions such as the MPR, DPR, and DPD based on the 1945 Constitution of the Republic of Indonesia, also become an academic discourse concerning what kind of parliament system used in Indonesian parliament. Therefore, it is necessary to examine the existing theories on the parliament system and how it implemented, especially in Indonesia. Based on the background above, this research aims to find out and understand the theories and experts thought on parliament, as well as to find out and understand the implementation of parliament system in Indonesia, viewed from the historical-judicial approach. Conceptually, the theories concerning parliament can be traced since the time of Ancient Greece. Moreover, several theories regarding parliament developed, such as accommodation of group interests in the parliament, and theory on division of parliament chambers. Regarding the implementation of parliament system in Indonesia, historically and judicially, it has its own dynamics, especially in the context of accommodation of group interests and the practice of parliament chambers’ division. For instance, in the early independence period and after the stipulation of 1959 Presidential Decree, the system reflected was unicameral, while during the 1949 Constitution of RIS period was bicameral system. Furthermore, after the amendment of the 1945 Constitution of Indonesia, there is also a discourse concerning the form of parliament division that applied, whether it was unicameral, bicameral, or tricameral. Intisari Ide mengenai Parlemen, cabang pemerintahan yang berkuasa membuat dan mengubah undang-undang, telah menjadi topik perdebatan bagi para sarjana sejak zaman dulu kala. Artikel ini bermaksud untuk menceritakan secara singkat tentang perkembangan konsep lembaga legislatif dan menjelaskan dinamikaperkembangan sistem parlemen di Indonesia dalam hukum konstitusi dari sudut pandang historis. Artikel ini menunjukkan bahwa Parlemen adalah institusi yang terus berkembang, dengan sistem bikameralisme yang tampaknya lebih cocok dengan sistem demokrasi perwakilan. Meskipun telah mempraktikkan sistem parlemen yang berbeda-beda dalam sejarahnya, sejak masa reformasi Indonesia lebih cenderung menganut sistem bikameralisme lunak.